Strategi Penguatan Pembangunan Madura Yang Berkelanjutan Melalui Pemberdayaan Nilai Kearifan Lokal - Abd Hannan (Universitas Trunojoyo Madura, 2018)
Being declared in 2015 in Rio De Janeiro, Brazil. development based Sustainable Development Goals (SDGs) has an aim to operate the development which is not only in progression but also in the orientation of maintenance of social area.Reaching the aim development based SDGs gives high response to universal development, emancipative, and participative that orientate to local wisdom value. This study focus on having an aim of analyzing on going Madura reinforcement through empowerment of local wisdom value. Several main issues become a focus of this analysis namely sustainable development concept, and the concept of local wisdom value. This study is descriptive study by library approach. The theory perspective of this study is development sociology theory. The finding of this study is about description concept and sustainable development theory; the explanation of local wisdom value in a system and social structure of Madura society; and descriptive analysis about sustainable development of Madura through empowerment of local wisdom value. Generally, this paper contributes of explaining the existence of local wisdom value in Madura development dynamic, and the explanation of social change of local society in sustainable development era.